Localising social work practice for migrant workers' children in China: An action research learning from other countries. (15th March 2022) - Huang, Xiwei; Jiang, Chenxi; Zhu, Xiaoxu
Abstract: While literature abounds in studying the phenomenon of migrant workers in China and offering policy suggestions from a macro perspective, this article proposes an inspiration for clinical social workers by developing a comprehensive case management model which aims at improving the well-being of migrant workers' children. It is argued that lessons could be learned from theories, methods and strategies to address immigration-related issues in the USA, Canada and some European countries, because migration patterns of China's migrant workers and international immigrants are similar. An action research approach is adopted. Unstructured interviews are conducted with clinical social workers, heads of social work organisations and schoolteachers. Based on the findings, a draft version of the case management model is constructed by borrowing immigrant social work methods selectively. As licensed social workers, the authors offer case management services to migrant workers' children and families under a social work agency's supervision in two urban–suburban-integrated schools. In the service process, the model is finished by modifications and localisation. The revised version of the model is elaborated in four steps. In each step, specific methods for migrant workers' children and families are presented with related case examples attached. Abstract : Whilst literature abounds in studying the phenomenon of migrant workers in China and offering suggestions from a macro perspective, this article offers an inspiration for clinical social workers by developing a comprehensive case management model which aims at improving the well-being of migrant workers' children. The authors identify similarities between migration patterns of China's migrant workers and international immigrants. It is argued that when traditional family processes are disrupted by either internal or international migration, the influences are similar and the necessity to fulfil family function remains the same. Theories, methods and strategies to address immigration-related issues have been well developed in local contexts of the USA, Canada and some European countries. Thus, the authors would like to try to shed some light on what lessons could be drawn. A draft version of this case management model is constructed by borrowing immigrant social work methods selectively. Based on the draft model, a team of licensed social workers offer case management services to migrant workers' children and families under a social work agency's supervision in two urban–suburban-integrated schools. In the service process, modifications and localisations were made. A revised model was presented in the article.